The Role of Health Cooperation in Building Aggregate Demand for Health Services - Asaad, Bassel Anwar; Dagher, Dana; Kashmar, Mohammad Bassam; Khadour, Zahraa Ammar (Magyar Gerontológia, 2025)
Working in a team greatly improves health cooperation and helps propose innovative solutions for health issues. Furthermore, a multidisciplinary team has more overlapping roles defined by communication and troubleshooting. However, Demand for health services is significant as it is related to the social aspect of citizens’ health status in a country. Since it is significant, the current study focuses on a very important problem, which is the possibility of estimating the total social demand for health services through public-private sector cooperation in third-world countries, represented by Syria. Moreover, it endeavors to propose a model for estimating the total social demand for health services in the public and private sectors. The descriptive analytical approach was used, and the data were collected through cooperation between a team of health experts in various fields, depending on the available secondary data, interviews, and the observation and estimation of the primary data. The model design includes dividing the total demand into six dimensions, which are (demand for hospitals, demand for health centers, demand for medical clinics, demand for dental clinics, demand for pharmacies, and demand for laboratories). The study has the following result: Health collaboration plays an important role in designing the proposed model and getting the missing health data needed.